Multiple Morphological Factors Underlie Experience-Dependent Cross-Modal Plasticity in the Developing Sensory Cortices. (11th December 2019) - Wang, Miao; Yu, Zixian; Li, Guangying; Yu, Xiang
Abstract: Sensory experience regulates the structural and functional wiring of sensory cortices. In previous work, we showed that whisker deprivation (WD) from birth not only reduced excitatory synaptic transmission of layer (L) 2/3 pyramidal neurons of the correspondent barrel cortex in mice, but also cross-modally reduced synaptic transmission of L2/3 pyramidal neurons in other sensory cortices. Here, we used in utero electroporation, in combination with optical clearing, to examine the main morphological components regulating neural circuit wiring, namely presynaptic bouton density, spine density, as well as dendrite and axon arbor lengths. We found that WD from P0 to P14 reduced presynaptic bouton density in both L4 and L2/3 inputs to L2/3 pyramidal neurons, as well as spine density across the dendritic tree of L2/3 pyramidal neurons, in the barrel field of the primary somatosensory cortex. The cross-modal effects in the primary auditory cortex were manifested mostly as reduced dendrite and axon arbor size, as well as reduced bouton density of L2/3 inputs. Increasing sensory experience by rearing mice in an enriched environment rescued the effects of WD. Together, these results demonstrate that multiple morphological factors contribute to experience-dependent structural plasticity during early wiring of the sensory cortices.